Need some help to make sure that I am doing this correctly.
PQ=QR ProvePR=QS ◄--------P-------Q----R--------S--------►
Statements Reasons PQ=RS Given Q is between PR midpoint R is between QS midpoint PQ=QR QR=RS PQ+QR=QR+RS Segment Addition Postulate (Postulate 1.13) PR=PQ+QR and QS=QR+QS Segment Addition Postulate (Postulate 1.13) PR=QS Substitution Law (Postulate 1.11)
Am I even on the right track?
If your statement of the hypotheses is correct, just "PR= QR", is correct, you can't prove "PR= QS", it isn't necessarily so! Nothing is said about "S" so it could be anywhere. For example supose the distance from P to Q and from Q to R is "1" Then the distance from P to R is 2 but we can choose S to make the distance from Q to S to be anything we like.
You say "Q is between PR" which makes no sense- PR is a number. What you want to say is that Q is between P and R. Same criticism of the next line but with the added point that there is nothing in your hypothesis that says that R is the midpoint of QS. Did your hypotheses include "QR= RS"? If so you had better add that!
You say "PQ= QR" and "given" which is correct. But you don't need to say later "QP= QR" (and you should never have "Reasons" left blank!).